Analisis Yuridis Pasal 44 Ayat 1 Undang-Undang RI N0. 23 Tahun 2004 Tentang Penghapusan Kekerasan Dalam Rumah Tangga (Studi Putusan Nomor: 292/Pidana Khusus/2021/Pengadilan Binjai) - Rolando Marpaung; Micael Jeriko Damanik; Maltus Hutagalung; Yestilia Dachi (Universitas Sari Mutiara Indonesia, 2023)
Domestic violence is an act of violence against someone, especially a woman, which results in misery, physical, sexual, psychological, financial suffering, and neglect of the household including threats to commit acts, and unlawful deprivation of liberty within the household sphere. The purpose of this study is to find out legal responsibility for perpetrators of crimes of domestic violence, to find out the legal basis for the panel of judges' considerations in imposing Decision Number 292 / Special Crimes / 2021 / Binjai Court, to find out how the law is applied to victims of domestic violence, This research method uses a qualitative method, meaning that it focuses more on legal analysis and examines legal materials, both from laws and regulations and books or documents related to this thesis. The conclusion of a criminal act is an act committed by someone who violates the law either intentionally or unintentionally and can be accounted for for his actions in accordance with the law which regulates a crime before the law.